Amil Zakat Professionalism in Post-Covid 19 Economic Recovery - Arie Sulistyawan Sulistyawan; Susi Widiasari (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
The professionalism of amil zakat in economic recovery during the Covid 19 pandemic is the goal of this research. A qualitative method with the type of literature research is used in this study because the data includes the author's experience and literature related to the investigation. The case of the Covid 19 pandemic that has never been felt in this country has made zakat amil move quickly to distribute zakat for the community's welfare and its economical application. The potential of zakat has not been achieved. At least zakat can show positive things for people who find it. That is the result of this study. As a result of the COVID-19 pandemic, the principles of professional zakat management institutions and the positive role of other parties are needed optimally to achieve higher zakat realization so that they can help the people's economy. For the potential of zakat to be maximized and increased, several things need to be improved, namely regarding zakat digitization, socialization, and innovation.